Simple Executive Function as an endophenotype of autism-ADHD, and differing associations between simple versus complex Executive Functions and autism/ADHD traits - Hendry, A; Bedford, R; Agyapong, M; Begum Ali, J; Bazelmans, T; Ersoy, M; Goodwin, A; Mason, L; Narvekar, N; Pasco, G; Johnson, MH; Jones, EJH; et al. (Nature Research, 2025)
Autism and ADHD are associated with difficulties with Executive Functions (EFs), but the prevalence and nature of these difficulties in early development is not well understood. In this longitudinal study, 107 children with a family history of autism and/or ADHD (FH-autism/ADHD), and 24 children with No-FH-autism/ADHD completed multiple EF tasks (5 at age 2 years, 7 at age 3 years). Parents reported on their child’s autism- (Q-CHAT at age 2, SRS-2 at age 3), and ADHD-related traits (CBCL DSM-ADHD scale, both ages). Compared to the No-FH-autism/ADHD group, the FH-autism/ADHD group showed lower scores on simple EFs (involving response inhibition, and holding in mind) at ages 2 and 3. Exploratory analysis linked FH-autism specifically with lower Executive Attention (top-down attentional control) at age 2, and the combination of FH-autism and FH-ADHD with lower Complex EF (involving selectively deploying responses, or updating information) at age 3. Three-year-olds’ Simple EF scores were negatively associated with ADHD-related traits. Complex EF scores were negatively associated with autism traits (before correcting for multiple comparisons). Toddlers with a family history of autism and/or ADHD may benefit from interventions to support simple EF development, whilst those already showing autistic traits may benefit from support with more-complex EF skills.